AaaS: uma nova condição para criar, conhecer, comunicar - Lopes, Vanessa (2012)
The technological, material and economical transformations that have marked the last decades changed the way that people create, store and share information due to the progress achieved by ICT (Information and Communication Technology). The objective of this dissertation is to test the new paradigm of Cloud Computing, from which new virtual architectures are built as on-‐demand services, involving creative processes and new communication procedures in digital environments. To do so, the dissertation proposes the principle of AaaS (Art as a Service) as an update to the discussions about art and media, exposing the recent transformations operating in the boundaries of media derivatives. The research presents an interdisciplinary bibliography which transits between studies in communication, art and culture. In conceptual terms, it departs from the understanding of artmedia, proposed by Arlindo Machado (2009), from the concepts of world-‐culture and hypermodernity pointed by Gilles Lipovetsky and Jean Serroy (2010) and from the studies of the post-‐media condition, elaborated by art critic Rosalind Krauss (2000). The research corpus is composed by experiments on ambient, materiality and image but without holding on to specific media or genres. These are analysed, not only from a theoretical point of view, but also from a practical methodology which testing the cloud-‐map configuration in the second chapter. In line with these movements, we sought to collaborate with the network of critics, curators, artists, producers and institutions that have launched a new view on the theme, identifying the confluences and incompatibilities between the diverse fields involved